2021
DOI: 10.1177/13524585211029860
|View full text |Cite
|
Sign up to set email alerts
|

Artificial double inversion recovery images for (juxta)cortical lesion visualization in multiple sclerosis

Abstract: Background: Cortical lesions are highly inconspicuous on magnetic resonance imaging (MRI). Double inversion recovery (DIR) has a higher sensitivity than conventional clinical sequences (i.e. T1, T2, FLAIR) but is difficult to acquire, leading to overseen cortical lesions in clinical care and clinical trials. Objective: To evaluate the usability of artificially generated DIR (aDIR) images for cortical lesion detection compared to conventionally acquired DIR (cDIR). Methods: The dataset consisted of 3D-T1 and 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…On the other hand, no significant difference in the number of detected plaques between both sequences in the deep white matter (p = 0.344) and deep gray matter MS plaques (p = 0.104) (Figs. 1,2,3,4,5,6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, no significant difference in the number of detected plaques between both sequences in the deep white matter (p = 0.344) and deep gray matter MS plaques (p = 0.104) (Figs. 1,2,3,4,5,6).…”
Section: Resultsmentioning
confidence: 99%
“…We recommended that using artificial DIR, which can create high contrast images from standard input, can detect cortical lesions with high reliability, significantly improving lesion detection in MS patients [5,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of synthDIR to outperform FLAIR, a sequence still considered gold-standard in MS imaging, has been shown for a multi-modal input (T1w, T2w, and FLAIR) in a monocentric setting ( Finck et al, 2020 ; Bouman et al, 2021 ). In doing so, relevant reductions in scan times are feasible as the physical acquisition of 3D and isotropic DIR may take up to 7 min ( Eichinger et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that synthesizing DIR images with generative adversarial networks (GANs), a deep learning (DL) architecture with great potential for image synthesis, is feasible and improves lesion detection compared to FLAIR and T2w sequences ( Finck et al, 2020 ; Bouman et al, 2021 ). Nonetheless, and in particular as MS lesions typically are small, GANs are at risk to synthesize images of high morphologic similarity to the target image, while failing to translate the clinically important MS lesions.…”
Section: Introductionmentioning
confidence: 99%